Upgrading the virtual instrumentation of high voltage AC and impulse test using LabVIEW - Mohd Suhaimi, Mohamad Hafizuddin (2017)
Virtual Instrumentation has become an advancement application for the interface monitor and control electrical instrument system. This paper describes the significant of upgrading the Virtual Instrument of high voltage AC and impulse generator by designing the support analysis tool (external data storages) with the use of LabVIEW software. Impulse test unit had been supplied with a support virtual instrumentation, which is used a standard command program instrument C++ programming. Unfortunately, the virtual instrument is not applicable due to the command language used, which is in Japanese. As for the consequences, the users will collect the data manually for analysis process. In order for future usage high voltage lab for research and study the computer support program was upgraded by replacing the existing system with the Virtual instrumentation (VI).LabVIEW software is one of the platform that used in graphical programming that will ease the users. In addition, LabVIEW software provides a supports tool that simplified the method for interfacing instruments. Designs of virtual oscilloscope have been proposed as the analysis tool, which is use a direct USB interconnect and LabVIEW Plug and Play Instrument drivers. The virtual instrumentation designs have been justify by comparing the signal acquire with the actual oscilloscope. Furthermore the virtual instrumentation was simulated in real time for display and acquires signal waveform.